Comparison of iPad applications with traditional activities using person-centred care approach: Impact on well-being for persons with dementia. (March 2014) - Leng, Fong Yoke; Yeo, Donald; George, Stacey; Barr, Christopher
Professionals working with people with dementia need to develop new activities that occupy patients and increase positive emotions. Dementia care mapping is a reliable method of measuring well-being during activities with people with dementia. The iPad has many applications that may be suitable as a group activity for persons with dementia. Six people with dementia took part in two traditional and two iPad activities over two days. Well-being was recorded using dementia care mapping. Subjects displayed similar or better levels of well-being during iPad activities than traditional activities. A larger variation of behaviors was seen during iPad activities than traditional activities. With detailed planning using a person-centred care approach, iPad group activity has the potential to be as effective and engaging as other conventional activities in achieving well-being.